Students' Ten Motivations to Memorize Quran: A Case Study of Rumah Quran in Padang Indonesia - Mutathahirin, Mutathahirin; Muliati, Indah; Hasnah, Hasnah; Oktavia, Gifa (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2022)
This research aims to find out students' motivation in memorizing Quran at An-Nazhifa and Serambi Minang, Padang, Indonesia. This research used a qualitative method with the case study approach. The data was collected from forty-eight samples through deep interviews chosen by purposive sampling. Fourty-eight samples are the management of Rumah Quran, six of them are ustadz and ustadzah, twenty students and twenty of them are students' parents. The result of the interview will be analyzed by using NVivo12. Overall, the analysis of the research shows that there are ten students’ motivations, such as i) getting a reward by reading Quran, ii) becoming a theologian, iii) becoming a hafiz, iv) achieving goals easier, v) making parents happy, vi) get a chance to help their parents on the afterlife, vii) to study and get the scholarship, ix) family's encouragement, x) want to be Quran's teacher. These motivations can be the encouragement for the students to be hafiz Quran. Hopefully, this research can be a reference for the teacher and parents to encourage their children in memorizing Quran